The use of systematic reviews and other research evidence in disasters and related areas: preliminary report of a needs assessment survey. - CLARKE, MICHAEL (My University, 2013)
Objectives: This paper presents the initial data analysis for a survey to identify the attitudes towards systematic reviews and research of those involved in the humanitarian response to natural disasters and other crises; their priorities for evidence, and their preferences for accessing this information. Methods: Snowballing sampling techniques were used to recruit participants who identified themselves as humanitarian aid workers, with or without experience in providing funding to aid agencies. An online questionnaire with both quantitative and qualitative questions was made available to participants using a variety of e-mail lists. Quantitative responses from 85 participants to a selection of questions were descriptively analysed using SPSS. Results: Findings indicated that respondents had positive opinions about systematic reviews and using research evidence when planning and responding to disasters. Seventy participants answered the question on the usefulness of reviews before, during and after disasters and, of these, 83% said that systematic reviews are useful in disasters, and the remaining 17% said they did not know. No-one selected the option that systematic reviews are not useful. The most preferred format for access to systematic reviews was the whole reviews, supplemented by comments from experts in the humanitarian sector (61%), 33% choose access to the full review, 20% choose the summary of reviews and 50% choose summary of reviews plus context-specific information. Inadequate access was the most commonly reported barrier to the use of systematic reviews (70%). This was followed by the lack of time to use reviews (59%) and insufficient knowledge about reviews (49%). Respondents selected scientific evidence as the most preferred type of evidence for influencing their decisions (80%), 11% ranked personal experience highest, 6% said their organisation’s usual practice, 1% said anecdotal evidence and 1% said intuition would be their first choice. 69% of participants “strongly agreed” that evidence from systematic reviews could have a positive role in humanitarian interventions and a further 29% “agreed” with the same statement. 66% thought they would like to access them when a natural disaster is not known to be imminent, compared to 34% who said that they would not wish to access systematic reviews at such a time. 70% would like to access systematic reviews during the period of prediction that a disaster will happen Conclusion: These preliminary findings from the Evidence Aid survey emphasise the need for “global” evidence but also the need that this be supplemented by local and context-specific knowledge. Systematic reviews could play a central role in improving the effectiveness of humanitarian aid in the planning, delivery and recovery phases of a disaster.
PUBLISHED
Keywords: systematic review; delivery and recovery; humanitarian planning; Evidence base